Enterocytozoon Bieneusi Infects Children With Inflammatory Bowel Disease Undergoing Immunosuppressive Treatment - Zajączkowska, Żaneta; Akutko, Katarzyna; Kváč, Martin; Sak, Bohumil; Szydłowicz, Magdalena; Hendrich, Andrzej B; Iwańczak, Barbara; Kicia, Marta (Frontiers in medicine, 2021)
Objectives: Patients with inflammatory bowel disease (IBD) are susceptible to intestinal opportunistic infections due to both defective mucosal immunity and altered immune response resulting from immunosuppressive treatment. Microsporidia infecting the gastrointestinal tract and causing diarrhoea can potentially affect the course of IBD. Methods: Stool samples (90 IBD children and 121 healthy age-matched controls) were screened for Encephalitozoon spp. and Enterocytozoon bieneusi by microscopy and polymerase chain reaction followed by sequencing. Results:E. bieneusi genotype D was found in seven out of 90 (7.8%) IBD children. No children from the control group were infected, making the pathogen prevalence in the IBD group significant (P = 0.002). Furthermore, infection was confirmed only in patients receiving immunosuppressive treatment (P = 0.013). Conclusions: Children with IBD are at risk of intestinal E. bieneusi infection, especially when receiving immunosuppressive treatment. Therefore, microsporidia should be considered as a significant infectious agent in this group of patients.